The Impact of Domestication on Aboveground and Belowground Trait Responses to Nitrogen Fertilization in Wild and Cultivated Genotypes of Chickpea (Cicer sp.) - Marques, Edward; Krieg, Christopher P.; Dacosta-Calheiros, Emmanuel; Bueno, Erika; Sessa, Emily; Penmetsa, R. Varma; von Wettberg, Eric (Frontiers in Genetics, 2020)
Despite the importance of crop responses to low fertility conditions, few studies have examined the extent to which domestication may have limited crop responses to low-fertility environments in aboveground and belowground traits. Moreover, studies that have addressed this topic have used a limited number of wild accessions, therefore overlooking the genotypic and phenotypic diversity of wild relatives. To examine how domestication has affected the response of aboveground and belowground agronomic traits, we measured root and leaf functional traits in an extensive set of wild and domesticated chickpea accessions grown in low and high nitrogen soil environments. Unlike previous studies, the wild accessions used in this study broadly capture the genetic and phenotypic diversity of domesticated chickpea’s (Cicer arietinum) closest compatible wild relative (C. reticulatum). Our results suggest that the domestication of chickpea led to greater capacities for plasticity in morphological and biomass related traits but may have lowered the capacity to modify physiological traits related to gas exchange. Wild chickpea displayed greater phenotypic plasticity for physiological traits including stomatal conductance, canopy level photosynthesis, leaf level photosynthesis, and leaf C/N ratio. In contrast to domesticated chickpea, wild chickpea displayed phenotypes consistent with water loss prevention, by exhibiting lower specific leaf area, stomatal conductance and maintaining efficient water-use. In addition to these general patterns, our results indicate that the domestication dampened the variation in response type to higher nitrogen environments for belowground and aboveground traits, which suggests reduced genetic diversity in current crop germplasm collections.